The Impact Of Storage On The Purpleness Of Cocoa Beans And Level Of Insect Damage In Stored Cocoa Beans - Mbahi, E.B. (University of Ghana, 2013)
Cocoa is one of the most important cash crops in West Africa especially Ghana. It contributes 23% of the foreign export earnings from the agricultural sector in Ghana. Cocoa beans are fermented and dried before exporting. The fermentation period in Ghana is 6 to 7 days but some cocoa farmers under-ferment their cocoa beans leading to the development of purple cocoa beans. This study was carried out at CRIG and African Regional Postgraduate Programme in Insect Science (ARPPIS) at the University of Ghana to determine the impact of storage period and level of insect infestation on the level of purple cocoa beans. Cocoa beans taken from ripened pods were fermented for 1, 2, 3, 4 and 5 days to get the purple beans for the experiment and were sundried. Ephestia cautella and Tribolium castaneum, both singly and in combination, were introduced into the cocoa beans at the beginning of the storage and stored for 120 days. Cut test was used to determine the level of purpleness of the dry cocoa beans. Insect numbers were counted and the contaminants produced by these insects were observed. Percentage weight loss of the cocoa beans was determined using Count and Weigh method. Cocoa beans infested with E. cautella alone had the highest population of 297 ± 22.7. The highest weight loss was recorded in cocoa beans fermented for one and four days (10.1 ± 1.87% and 10.1 ± 8.74%). The population of E. cautella and weight loss increased with storage period. There was variation in the percentage of purple beans during the storage period. Cocoa beans fermented for 3 and 4 days had the highest percentage of purple beans. Cocoa beans fermented for one and two days were considered as slaty beans. Although there was variation in the percentage of purple beans, the grade of the beans did not vary. Tribolium. castaneum which is also a major pest of stored cocoa beans did not cause much damage to the whole cocoa beans but E. cautella alone caused significant damage to stored cocoa beans. The study was conducted using grade II cocoa beans but the cocoa beans deteriorated over the storage period to sub-standard due to high levels of other defects such as germinated, flat and insect infested cocoa beans. High insect infestation contributed a great deal to the reduction in quality. From this study, poor fermentation and insect infestation are a great threat to the quality of cocoa beans. There was no significant reduction in the percentage purple beans over the storage period. Storage therefore had no impact on the percentage of purple cocoa beans. More attention should be given to E. cautella in terms of control.
Thesis (MPhil)
Keywords: Storage; Purpleness Of Cocoa Beans; Insect Damage; Cocoa Beans